Association of urinary incontinence with depression among men: a cross-sectional study - Shasha Wu; Feixiang Wu (BMC, 2023)
Abstract Objective Depression and urinary incontinence (UI) are both troubling symptoms that severely impact quality of life. The aim of this study is to evaluate the association between UI (including UI types and severity) and depression among men. Population and methods The analyzed data was collected from the 2005-2018 National Health and Nutrition Examination Survey (NHANES) data. A total of 16,694 male participants aged ≥ 20 years with complete information about depression and UI were included in this study. Logistic regression was performed to calculate the odds ratio (OR) and 95% confidence interval (CI) to determine the association between depression and UI by adjusting for relevant covariables. Results The prevalence of depression was 10.91% among participants with UI. Urge UI was the main type of UI and accounts for 50.53% of all UI types. The adjusted ORs for the association between depression and UI were 2.69 (95%CI, 2.20-3.28). Compared with slight UI, the adjusted ORs were 2.28 (95% CI, 1.61-3.23) for moderate UI, 2.98 (95% CI, 1.54-5.74) for severe UI, and 3.85 (95% CI, 1.83-8.12) for very severe UI. Compared with no UI, the adjusted ORs were 4.46 (95% CI, 3.16-6.29) for mixed UI, 3.15 (95% CI, 2.06-4.82) for stress UI, and 2.43 (95% CI, 1.89-3.12) for urge UI. The subgroup analyses also showed similar correlation about depression and UI. Conclusion Among men, depression was positively associated with UI status, severity and types. For clinicians, it's necessary to screen depression in patients with UI.